Efficacy and safety of a novel TKI (anlotinib) for the treatment of advanced digestive system neoplasms: a systematic review and meta-analysis - Zhou, Changhui; Wang, Weihua; Mu, Ying; Meng, Min (Frontiers in Immunology, 2024)
Objective: To systematically evaluate the efficacy and safety of anlotinib targeted therapy for the treatment of patients with advanced digestive system neoplasms (DSNs).: Clinical trials were extracted from PubMed, the Cochrane Library, Web of Science, EmbaseEMBASE, China National Knowledge Infrastructure (CNKI)CNKI and the Wanfang database up to October 2023. Outcome measures, including therapeutic efficacy, quality of life (QOL) and adverse events, were extracted and evaluated. Results: Twenty trials, including 1,613 advanced DSNs patients, were included. The results indicated that, compared with conventional treatment alone, the combination of anlotinib targeted therapy with conventional treatment significantly improved the patients' 6-months overall survival (OS, OR=1.76, CI=1.53 to 2.02, P<0.00001), overall response (ORR, OR=1.76, CI=1.53 to 2.02, P<0.00001) and disease control rate (DCR, OR=1.51, 95% CI=1.25 to 1.84, P<0.0001). Moreover, the group that received the combined therapy had higher rates of hypertension (P<0.00001), proteinuria (P<0.00001), fatigue (P<0.00001), diarrhea (P<0.00001), hypertriglyceridemia (P=0.02), alanine aminotransfease (ALT)ALT increased (P=0.004), aspartate transaminase (AST) AST increased (P=0.006), anorexia (P<0.00001), weight loss (P=0.002), abdominal pain (P=0.0006), hypothyroidism (P=0.02), prolonged QT interval (P=0.04), ). whereas aAnalyses of other adverse events, such as gastrointestinal reaction, Leukopenialeukopenia, and 3 Neutropenianeutropenia, et al did not reveal significant differences (P>0.05).The combination of anlotinib targeted therapy and conventional treatment is more effective for DSNs treatment than conventional treatment alone.However, this combined treatment could lead to greater rates of hypertension, albuminuria and hand-foot syndrome. Therefore, the benefits and risks should be considered before treatment.